Effect of heat treatment on the corrosion resistance of aluminium alloys - Ahmad Zul Hafiz, Ramli (2010)
Aluminium alloy 5083 is commonly used in the ships and boats in the marine environment and susceptible to corrosion when they are run at high speed velocity and high flow rate condition. The purpose of this study is to investigate the effect of solution heat treatment on the corrosion resistance of aluminium alloys by using aluminium 5083 as a material for the experiments. The objective of this study is to investigate the corrosion resistance by differing the aging time during solution heat treatment process and to determine the corrosion rate by using immersion test method. The microstructures of heat treated specimens have been observed using metallurgical microscope and scanning electron microscope while the hardness test has been done using Vickers hardness tester. The corrosion rates of the heat treated specimens were determined using weight loss method. The corrosion resistance of heat treated specimens increased after solution heat treatment while the hardness of the specimens slightly decreased. The type of corrosion occurred on the surface of specimens were found to be uniform corrosion